A gamma-ray imaging camera for NORM radioactivity detection. (December 2020) - Altomare, C; Di Venere, L; Fanchini, E; Giordano, F; Loparco, F; Morichi, M; Pantaleo, F R; Spinelli, P; Swiderski, L
Abstract: Naturally occurring radioactive materials ( NORM ) and technologically enhanced naturally occurring radioactive materials ( TENORM ) consists of materials enriched with radioactive elements, found in the environment, with concentrations over the ambient natural radioactivity average, such as industrial wastes and extraction byproducts. We designed a camera for gamma-ray imaging and radionuclide identification based on the coded mask technique. The camera proposed is a compact, lightweight instrument, ideal for real-time analysis, with a low power consumption, suitable for industrial process and ambient monitoring. We built a prototype consisting in 16 CsI(Tl) scintillators coupled to photo-multiplier tubes (PMTs) with a digital readout. We used a 7 × 7 mask composed by transparent and opaque tiles to encode radioactive gamma-rays sources image and use a reconstruction algorithm for decoding. The system was first tested using free gamma-ray radioactive sources placed at a fixed distance from the mask and than, the same sources, was placed inside an industrial nuclear waste drum to test shielding and detection limit. We will also show the results with a NORM igneous rock sample and we will try to identify the radioactive sources after a estimation of the count rate over the background, the test was carried out in lead chamber to shield the natural laboratory background. The performance of the prototype camera in terms of energy and spatial resolution with respect the detection time will be shown.